Reconstituting Pedagogical Authority in the GenAI Era: Intelligent-TPACK, Deep Learning, and the Ethical-Cultural Knowledge of Maja Labo Dahu in Islamic Religious Education - Lalu Muttaqin; Nasaruddin Nasaruddin; Syarifuddin Syarifuddin (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2026)
The diffusion of generative artificial intelligence (GenAI) into classrooms has produced inverted authority, a structural gap in which students' digital fluency outpaces teachers' technical mastery, placing particular pressure on Islamic Religious Education (IRE), where the teacher conventionally serves as the primary interpretive authority. No existing framework integrates AI-enabled teaching competence, deep-learning pedagogy, and culturally grounded moral resilience into a single coherent model. This qualitative case study examined how eleven IRE teachers at MAN 2 Kota Bima (West Nusa Tenggara, Indonesia) negotiate these pressures through the Mbojo philosophy of Maja Labo Dahu. Following critical-case logic, data were collected via semi-structured interviews, non-participant classroom observation (24 sessions), and an open-ended student survey (n = 93; January–March 2026), and analysed using the Miles–Huberman–Saldaña interactive model. Three findings emerged: pedagogical authority is reconstituted through reverse mentoring grounded in tawāḍuʿ (humility), confirmed across 14 of 24 observed sessions; deep-learning pedagogy is operationalised through a